ANALISIS PENGARUH BRAND AMBASSADOR SONG JOONG KI, KUALITAS PRODUK, DAN ELECTRONIC WORD OF MOUTH (EWOM) TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK SCARLETT WHITENING DI TANGERANG SELATAN - Selly Iyumi Natasya Mahmud (2022)
This quantitative research was to test whether or not the influence of brand ambassadors, product quality, and EWOM on purchasing decisions. The population is Scarlett Whitening users who live in South Tangerang. The sample in this study amounted to 75 respondents, the probability sampling method used the purposive sampling method. The technique for collecting data is done by distributing Google Forms through social media. The data were analyzed using the PLS method with the help of SmartPLS 3.0 software. The results of the research indicate that (1) Soon Joong Ki's brand ambassador has a joint influence and a positive direction on purchasing decisions, namely 0.210 (2) product quality has a joint influence and a positive direction on purchasing decisions, namely 0.340 (3) EWOM has a significant influence and a positive direction on purchasing decisions of 0.451.